Fracture predictions in impact three-point bending test of European beech - Kubík, Petr; Šebek, František; Hassan Vand, Mojtaba; Brabec, Martin; Tippner, Jan (Springer Nature, 2024)
Hardwood has become widespread in European forests. The strongest factor is climate change and damage to conifers by the bark beetle. The effort to study hardwoods grows with increasing volume of applications. Therefore, European beech wood was investigated under two impact loads in two material directions, resulting in four unique combinations supplemented by the measurement of the friction coefficient. Then, it was computationally simulated to reproduce the cracking, while the material model reflected the orthotropic behaviour in elasticity, plasticity and failure. The model was coded using the user subroutine in Abaqus to initiate and propagate the crack using the element deletion. The resulting reaction forces were in good agreement with those from the experiments. Cracking was numerically simulated in three of four cases as experimentally observed, however, upon larger deflections. Therefore, the model is applicable for further investigations.

Hardwood has become widespread in European forests. The strongest factor is climate change and damage to conifers by the bark beetle. The effort to study hardwoods grows with increasing volume of applications. Therefore, European beech wood was investigated under two impact loads in two material directions, resulting in four unique combinations supplemented by the measurement of the friction coefficient. Then, it was computationally simulated to reproduce the cracking, while the material model reflected the orthotropic behaviour in elasticity, plasticity and failure. The model was coded using the user subroutine in Abaqus to initiate and propagate the crack using the element deletion. The resulting reaction forces were in good agreement with those from the experiments. Cracking was numerically simulated in three of four cases as experimentally observed, however, upon larger deflections. Therefore, the model is applicable for further investigations.
Fracture predictions in impact three-point bending test of European beech
Keywords: Anisotropy; Barlat; Dynamic; Explicit; Flexure; Rupture; Anisotropy; Barlat; Dynamic; Explicit; Flexure; Rupture